A note on population pharmacokinetic studies with a single sampling design - Narukawa, Mamoru; Yafune, Akifumi (Therapeutic drug monitoring, 2005)
The choice of sampling time point in a population pharmacokinetic study with severe limitation on the number of samples per study subject (single sampling design) is critical in obtaining reliable parameter estimates. The authors have investigated the relationship between the timing as well as the degree of distribution of a sampling point among study subjects and the reliability of the estimates of pharmacokinetic parameters in a population pharmacokinetic study. This was achieved through a simulation, assuming an intravenously administered drug whose pharmacokinetic profile follows a 1-compartment model. The convergence rate of the NLMIXED procedure as well as the values of bias and MSE for the estimated parameters showed great variability depending on the sampling schedules. The results indicate that, in the case of a single sampling design, the sampling points should be distributed as widely as possible over a time range along the concentration-time profile to obtain reliable parameter estimates.